Evolution of Phototrophy in the Chloroflexi Phylum Driven by Horizontal Gene Transfer - Ward, Lewis M.; Hemp, James; Shih, Patrick M.; McGlynn, Shawn E.; Fischer, Woodward W. (Frontiers in Microbiology, 2018)
The evolutionary mechanisms behind the extant distribution of photosynthesis is a point of substantial contention. Hypotheses range from the presence of phototrophy in the last universal common ancestor and massive gene loss in most lineages, to a later origin in Cyanobacteria followed by extensive horizontal gene transfer into the extant phototrophic clades, with intermediate scenarios that incorporate aspects of both end-members. Here, we report draft genomes of 11 Chloroflexi: the phototrophic Chloroflexia isolate Kouleothrix aurantiaca as well as 10 genome bins recovered from metagenomic sequencing of microbial mats found in Japanese hot springs. Two of these metagenome bins encode photrophic reaction centers and several of these bins form a metabolically diverse, monophyletic clade sister to the Anaerolineae class that we term Candidatus Thermofonsia. Comparisons of organismal (based on conserved ribosomal) and phototrophy (reaction center and bacteriochlorophyll synthesis) protein phylogenies throughout the Chloroflexi demonstrate that two new lineages acquired phototrophy independently via horizontal gene transfer (HGT) from different ancestral donors within the classically phototrophic Chloroflexia class. These results illustrate a complex history of phototrophy within this group, with metabolic innovation tied to HGT. These observations do not support simple hypotheses for the evolution of photosynthesis that require massive character loss from many clades; rather, HGT appears to be the defining mechanic for the distribution of phototrophy in many of the extant clades in which it appears.